A time-series and cross-sectional momentum strategy: Dual momentum applied from a South African perspective - Fuchsloch, Michael (Department of Finance and Tax, 2023)
Fama and French (2008, p.1654) referred to momentum as a “premier market anomaly”. The momentum effect has been nearly universally observed across all asset classes globally (Asness, et al., 2013). This research paper further explores momentum and replicates the dual momentum strategy proposed by Antonacci (2014) within a South African context. Dual momentum combines time-series and cross-sectional momentum in pursuit of enhanced risk adjusted returns. The strategy is constructed using tradeable indices in order to minimise transaction costs. This study investigates the dual momentum strategy applied to the JSE Top 40 index. The strategy also includes two indexes which stay constant, the MSCI ACWI index for offshore exposure and the STeFI index which serves as an alternative proxy investment and acts as a safe haven during economic downturn. In addition, this study investigates two variations of the core strategy which include shortening the look-back period and lowering the strategy's threshold. Furthermore, and supplementary to the core strategy, dual momentum is applied to several South African sector indexes. Followed by a second supplementary section where dual momentum is applied to a pool of indexes where only the top performing index is used over a specific period in time. The results of the performance analysis of the dual momentum strategy over the sample period illustrates the strategy's ability to generate superior risk adjusted returns, lower standard deviations, lower maximum drawdowns, and yields significant positive alpha. Thus, the core dual momentum strategy and focal point of this study, validates the strategy within a South African context. However, the results of the variations and both supplementary sections display a vast range in underperformance. This highlights the dual momentum strategy's inability to adequately cope with high volatility. During periods of high volatility, the strategy tends to struggle which is also the case with the core strategy and most other momentum strategies. Therefore, the two variations and supplementary strategies do not manage to improve the core dual momentum strategy.